Resilience and academic self-efficacy in university students - Gallardo Chacón, Kevin Fernando; Vargas Espín, Alba del Pilar (Revista Ecos de la Academia, 2024)
This research aimed to relate resilience and academic self-efficacy in university students. It was a descriptive study with a correlational scope and cross-sectional design. Data were collected from 501 university students majoring in veterinary medicine and agronomy from a university in Ambato, Ecuador. The Wagnild and Young Resilience Scale (RS) and the Academic Situations-Specific Perceived Self-Efficacy Scale (EAPESA) were used. The results showed a moderate positive correlation between resilience and academic self-efficacy (p = < .001); regarding resilience, a high level prevailed at 64.1% (321), and for academic self-efficacy, an average score of 25.5 was found. No significant difference was identified in resilience based on gender. It is concluded that higher resilience corresponds to higher academic self-efficacy.